ADVANCES IN PEDIATRIC ONCOLOGY SCREENING AND TREATMENT (Neo Scientific Peer Reviewed Journal, 2024)
Pediatric oncology has witnessed significant advancements in recent years, particularly in the areas of screening, genetic analysis, and the development of novel treatment protocols. This paper examines the current state of these developments and their potential impact on improving outcomes for children with cancer. The continuing evolution of technology has revolutionized the field of pediatric oncology (Kulkarni, 2016). Advancements in bone marrow transplantation, supportive care, and the management of side effects and after-effects of cancer treatments have all contributed to improved outcomes for young patients. Furthermore, the era of precision medicine has dawned, with technology serving as the backbone for advancements in diagnostics, drug therapy, surgery, and radiation oncology. Specifically, the field of pediatric oncology has seen significant progress in the area of screening and early detection. Circulating tumor cells have emerged as a potential biomarker for early cancer detection and monitoring disease progression (Micalizzi et al., 2017). Nanotechnology has also shown promise in the development of innovative diagnostic platforms for the early detection of cancer. (Morris et al., 2014) Moreover, the application of genetic analysis and profiling technologies has allowed for the identification of specific molecular markers, which can inform personalized treatment approaches and improve outcomes for pediatric cancer patients. (Cruz & Peng, 2019).